2010
DOI: 10.2528/pierb10062105
|View full text |Cite
|
Sign up to set email alerts
|

A New Rain Attenuation Conversion Technique for Tropical Regions

Abstract: Abstract-Rain attenuation is one of the most crucial factors to be considered in the link budget estimation for microwave satellite communication systems, operating at frequencies above 10 GHz. This paper presents a mathematical model for converting terrestrial rain attenuation data to be used for satellite applications at Ku-band. In the proposed technique, the ITU-R P 618-9, together with a combination of ITU-R P 530-12 and the revised Moupfouma model have been adopted for satellite and terrestrial rain atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…The performance of communication links in frequencies above 5 GHz are affected by rain attenuation so the attenuation is one of the most crucial factors to be considered in the link budget estimation [1,2]. The rain attenuation is a function of raindrop, and consequently can be predicted when the DSD data are available [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of communication links in frequencies above 5 GHz are affected by rain attenuation so the attenuation is one of the most crucial factors to be considered in the link budget estimation [1,2]. The rain attenuation is a function of raindrop, and consequently can be predicted when the DSD data are available [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The significance of Figure 5 and Table V can be demonstrated as follows: The ITU-R specifies the availability of 99.99% (i.e, 0.01 % of the time in an average year) for commercial operators. Usually propagation impairments have a significant effect only for less than one percent of the time during a year; therefore the system gain must be enhanced through an additional fade margin to meet the desired availability and quality of service, QoS specifications [3]. For example, as shown The newly released ITU-R P.530-14 and three classical rain attenuation prediction models are validated in this article, using the data bank available from six geographically spread DIGI MINILINKs operating at 15 GHz in Peninsula Malaysia.…”
Section: B Experimental Proceduresmentioning
confidence: 99%
“…However, results from some recent researches have suggested that some ITU-R models may not necessarily be best suited or most reliable for all frequencies or in all geographical areas [14][15][16][17].…”
Section: An Overview Of Selected Rain Attenuation Prediction Modelsmentioning
confidence: 99%
“…Attenuation experienced in tropical areas is caused by considerably higher rainfall rates and bigger size of raindrops compared to other parts of the world [11]. Since the Ku frequency band (14/12 GHZ) has shown serious signs of depletion, research activity have since been directed towards the full utilization of the Ka band (30/20 GHz), while the V band (50/40 GHz) is being considered for applications in the near future [14]. Utilization of higher frequency bands such as the Ku band for satellite communication provides a number of important benefits.…”
mentioning
confidence: 99%